Association between neutrophil-to-lymphocyte ratio and diabetic retinopathy in patients with type 2 diabetes: a cohort study - Tang, Yuchen; Li, Li; Li, Jialin (Frontiers in Endocrinology, 2024)
Background: Chronic inflammation is implicated in the development of diabetic retinopathy (DR). The neutrophil-to-lymphocyte ratio (NLR) is a marker of systemic inflammation that has been linked to cardiovascular and diabetic kidney diseases. However, the link between NLR and DR remains unclear. As such, this study investigated the association between NLR and DR in Chinese patients. Method: A total of 857 adults diagnosed with type 2 diabetes mellitus (T2DM) without DR at baseline between 2018 and 2021, from a single center in Ningbo, China, were included. Baseline clinical data, including age, sex, T2DM duration, hypertension, smoking, drinking, glycated hemoglobin level, lipid profile, renal function, and NLR, were recorded and analyzed. Cox proportional hazard regression analysis was used to assess the association between NLR and the risk for incident DR. Results: During a median follow-up of 3.0 years, 140 patients developed DR. The multivariable-adjusted hazard ratio (HR) for incident DR across ascending NLR quartiles (≤1.46 [reference], 1.47–1.90, 1.91–2.45 and > 2.45) were 1.000, 1.327 (95% confidence interval [CI] 0.754–2.334), 1.555 (95% CI 0.913–2.648) and 2.217 (95% CI 1.348–3.649), respectively. For each 1-standard deviation increase in NLR, the risk for DR increased by 29.2% (HR 1.292 [95% CI 1.112–1.501) after adjusting for confounding factors. Conclusion: Results revealed that a higher NLR at baseline was associated with an increased risk for incident DR. NLR has the potential to be an inexpensive, reliable, and valuable clinical measure that merits further exploration in future studies.